Assessment tools and outcomes in real–world migraine patients eligible for treatment with an anti–calcitonin gene–related peptide antibody - Kasai Hideyo; Watanabe Keiko; Yasumoto Taro; Mizuma Keita; Futamura Akinori; Kuroda Takeshi; Yano Satoshi; Hieda Sotaro; Ono Kenjiro; Murakami Hidetomo (神経治療学, 2024)
Real–world clinical outcomes were examined in 96 patients with migraine who were eligible for treatment with anti–calcitonin gene–related peptide (CGRP) antibodies. In 71 patients who received this treatment, three assessment tools (Migraine Disability Assessment Scale (MIDAS), Headache Impact Test (HIT–6), and Visual Analog Scale (VAS)) were used to evaluate the efficacy of the drugs. The 25 patients who declined to take anti–CGRP antibody drugs were asked about the reasons for their refusal and issues about use of these drugs. Patients with episodic migraine (EM) or chronic migraine (CM) had significantly decreased monthly migraine days (MMD) and improved daily disability after treatment with Galcanezumab or Fremanezumab. The two drugs were rated as very effective migraine prophylactics. The 50% responder rate (50%RR) for patients with CM who received Galcanezumab in the first month was significantly lower than that for patients with EM, Galcanezumab was less responsive to treatment for patients with CM. This is also the first study to evaluate the degree of daily life disability using three assessment tools concurrently. The results showed that HIT–6 and VAS, which are one–month indicators, were more sensitive than MIDAS, which is a three–month indicator. The main concerns among patients for introduction of anti–CGRP antibody drugs were the high cost and the increased frequency of hospital visits. Therefore, reduction of costs and fewer visits are needed to promote use of anti–CGRP antibody drugs with high efficacy. 外来通院する片頭痛患者で抗calcitonin gene–related peptide（CGRP）抗体薬が適応であった96例を対象に実臨床における症状の評価方法と転帰を検証した．同薬を投与した71例（galcanezumab 38例，fremanezumab 33例）では3種類の指標（migraine disability assessment scale（MIDAS），headache impact test（HIT–6），visual analog scale（VAS））を用いて，投与開始後1，2，3ヵ月後にその予防効果を検証した．また同薬導入を拒否した25名の片頭痛患者に拒否理由についてアンケートを実施し，抗CGRP抗体薬の導入促進についての課題を考察した．抗CGRP抗体薬の効果については反復性片頭痛患者（epsodic migraine：EM），慢性片頭痛患者（chronic migraine：CM）ともに毎月の片頭痛日数（monthly migraine days：MMD）は有意に減少し，日常生活支障度も有意に改善していることからgalcanezumab，fremanezumabは片頭痛予防薬として有効性が高い薬剤と評価できた．また，最初の1ヵ月におけるいずれかの抗CGRP抗体製剤を投与したCM患者群，galcanezumabを投与したCM患者群の50%レスポンダー率（50%RR）はEM患者群よりも有意に低く，いずれかの抗CGRP抗体製剤を投与したCM患者群，galcanezumabを投与したCM患者は治療早期に反応しにくいことが示唆された．本検討は3種類の評価方法で日常生活支障度評価を行った初めての検討であるが，治療効果を捉える感度は，3ヵ月指標のMIDASより1ヵ月指標となるHIT–6やVASの方が優れていた．一方，抗CGRP抗体薬を拒否した患者では，負担と受診頻度が増える事が拒否の大きな理由であり，費用を抑える事，受診頻度が増えない工夫をする事が，高い予防効果を有する抗CGRP抗体薬の導入促進につながると思われた．